Towards a public debt policy in Italy - L. SPAVENTA (PSL Quarterly Review, 2013)
This paper represents the full report of a committee chaired by Luigi Spaventa, prepared for and presented to the Italian Treasury ministry in July 1989. The report falls into five chapters: the reasons for a public debt management policy in Italy; debt management policy and monetary policy - some institutional changes; types of securities; the working of the markets; institutional and organisational aspects of debt management.